STRATEGI PUBLIC SPEAKING MENJADI KOMUNIKATOR HANDAL PADA PENGELOLA TPQ BAITURRAHMAH: Public Speaking Strategies To Become A Reliable Communicator In The Manager Of TPQ Baiturrahmah - Pramelani; Muherni Asri Utami; Taqwa Sejati (Pakis Journal Institute, 2023)
Communication is a process that is able to explain who the actors are, what the message is, what channels are used and to whom the message is delivered. Then one type of communication we know is public communication, one example of public communication or also often called public speaking. In the discipline of communication, public speaking is one of the studies. Why do you need to study and know public speaking? Because public speaking is the art of speaking. This Community Service activity was carried out at TPQ Baiturrahmah. As for the content of this Community Service seminar, the theme is Public Speaking Strategy to become a reliable communicator for the management of TPQ Baiturrahmah. This theme was taken to see that public abilities and skills are still not possessed by ordinary people who do not have the opportunity to study formally in an educational environment. The results of holding the Community Service seminar are a form of activity for lecturers carrying out one of the academic responsibilities of higher education to the management of TPQ Baiturrahmah. It is hoped that they will be able to contribute regarding their skills in carrying out public communication. The service method consists of various kinds of preparation before activities, implementation of activities to evaluation activities. The results obtained from this activity provide participant and partner satisfaction where not only knowledge but also public speaking skills are gained.